2018
DOI: 10.1111/hel.12531
|View full text |Cite
|
Sign up to set email alerts
|

Effective antimicrobial activity of rifabutin against multidrug‐resistant Helicobacter pylori

Abstract: In vitro antimicrobial effectiveness of RFB on MDR H. pylori including those with resistance to both MTZ and CLR was demonstrated. However, RFB efficacy decreased as the number of antibiotics responsible for MDR increased. Considering that RFB inhibits both extra- and intracellular H. pylori, it can be suggested as an effective antibiotic against of MDR H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…From the 131 articles, 65 were excluded for the following reasons: meta‐analysis, review, non‐original research, conference abstract and article without full text (n = 55), and non‐relevant data or no data for susceptibility testing or no resistance data (n = 10). Finally, 66 studies 4,16‐80 were included in this systematic review and meta‐analysis (Supplementary Table ).…”
Section: Resultsmentioning
confidence: 99%
“…From the 131 articles, 65 were excluded for the following reasons: meta‐analysis, review, non‐original research, conference abstract and article without full text (n = 55), and non‐relevant data or no data for susceptibility testing or no resistance data (n = 10). Finally, 66 studies 4,16‐80 were included in this systematic review and meta‐analysis (Supplementary Table ).…”
Section: Resultsmentioning
confidence: 99%
“…35 WHO has categorized clarithromycin-resistant H. pylori to have severely impacted the health of human beings. 6 High primary resistance against clarithromycin (20.9%-96%) has been observed…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, only one strain was resistant to amoxicillin ( Hp1 strain), and no resistant strains to tetracycline were detected. In previous studies, the resistance rate to at least two antimicrobial agents were reported > 35% for H. pylori isolates [ 59 , 60 ]. Our results showed that five of the isolates were resistant to at least two antibiotics (35.7%).…”
Section: Discussionmentioning
confidence: 99%